Implications of Cognitive Load for Hypothesis Generation and Probability Judgment - Sprenger, Amber M.; Dougherty, Michael; Atkins, Sharona M.; Franco-Watkins, Ana M.; Thomas, Rick; Lange, Nicholas; Abbs, Brandon (Frontiers in Psychology, 2011)
We tested the predictions of HyGene (Thomas, Dougherty, Sprenger, & Harbison, 2008) that both divided attention at encoding and judgment should affect degree to which participants’ probability judgments violate the principle of additivity. In two experiments, we showed that divided attention during judgment leads to an increase in subadditivity, suggesting that the comparison process for probability judgments is capacity limited. Contrary to the predictions of HyGene, a third experiment revealed that divided attention during encoding leads to an increase in later probability judgment made under full attention. The effect of divided attention at encoding on judgment was completely mediated by the number of hypotheses participants generated, indicating that limitations in both encoding and recall can cascade into biases in judgments.